Предмет: Алгебра,
автор: ulia198231
(ax-1)=(x-3) как решить
Ответы
Автор ответа:
0
(ax-1)=(x-3)
ax-x=-3+1
a=2
Автор ответа:
0
(ax-1)=(x-3)
(ax-1)-(x-3)=0
ax^2-3ax+x-3=0
ax^2-2ax-3=0
D=-(2^2)-4*1*(-3)=4+12=16
X1=2-4\2=-3
X2= 2+4\2=3
mandarin4ck:
Ну вот и все! Если не понятно,то извини
Похожие вопросы
Предмет: Українська мова,
автор: XIROI4EK
Предмет: Литература,
автор: samurai14anime
Предмет: Другие предметы,
автор: VarvaraSalina
Предмет: Математика,
автор: YoloseLnk
Предмет: Математика,
автор: Mlss10